EKSPOSUR NILAI TUKAR DOLAR (US$) PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - Mata, Vivilia Wulandari Tarru; Pangeran, Perminas (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT This research was intended to test the dollar (US$) foreign exchange exposure towards the multinational company in Indonesia. This research used theory of hedging policy about the foreign exchange exposure. Foreign exchange exposure could be explained by the companyÃ¢â¬â¢s internal variables, which are size, dividend payout ratio (DIV), quick ratio (QR), a market-to-book equity ratio (MBE) and long-term debt ratio (DE). The results showed that the dividend payout ratio and market-to-book equity ratio had an influence on the level of foreign exchange exposure. Keywords: foreign exchange exposure, hedging